Seroprevalence of Schmallenberg virus in the United Kingdom and Republic of Ireland: 2011-2013 - King, Barnabas; O'Shea Brown, Thomas; Tarlinton, R.E.; Daly, Janet M. (Elsevier, 2015)
Since its identification in late 2011, Schmallenberg virus (SBV) spread rapidly across Europe. Using archived samples from domestic ruminants collected between October 2011 and June 2013, the seroprevalence in the United Kingdom (UK) and Republic of Ireland (IE) was estimated using a serum neutralisation test. There was no significant difference (P > 0.05) in seroprevalence between sheep and cows suggesting that neither species is significantly more at risk of SBV infection in the UK. A single 2011 sample tested positive; the sample was taken in November from a cow in Wiltshire. There was a steady increase in overall seroprevalence during the first three quarters of 2012, which then more than doubled in quarter 4 (October–December), which may reflect a peak of vector activity. By the end of June 2013, overall seroprevalence was around 72%. However, although seroprevalence was over 50% in Wales and southern and central counties of England, it was below 50% in all other areas of the UK and IE. This suggests that there were still substantial numbers of animals at risk of infection in the latter half of 2013.